The Tales that Bind : A Narrative Model for Living and Helping in Rural Communities - Randall, William Lowell, 1950-; Furlong, Dolores; Clews, Rosemary A. (Rosemary Arrowsmith), 1944-2012 (Book collections on Project MUSE., 2015)
The Tales that Bind presents a narrative approach to facing the challenges of working as a practitioner in social work, education, medicine, or the church in small towns, remote hamlets, and other rural settings.